2000
DOI: 10.1021/ic000770b
|View full text |Cite
|
Sign up to set email alerts
|

Silver(I) Complexation of (Poly)aromatic Ligands. Structural Criteria for Depth Penetration into cis-Stilbenoid Cavities

Abstract: Silver(I) complexes with aromatic donors are thoroughly analyzed (with aid of the Cambridge Crystallographic Database) to identify the basic structural factors inherent to the bonding of an arene ligand. Most strikingly, the distance parameter d (which simply measures the normal separation of Ag from the mean aromatic plane) is singularly invariant at d = 2.41 +/- 0.05 A for all silver/arene complexes, independent of the hapticity (eta 1 or eta 2), hybridization, or multiple coordination. As such, a systematic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
110
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(118 citation statements)
references
References 48 publications
8
110
0
Order By: Relevance
“…3. At this point it should be noted that the ''central'' cation Ag + is bound at the edges of the terminal [6]helicene aromatic rings, the corresponding hapticity of these bonds being g 2 , which follows from previous results by Lindeman et al [42]. The closest carbon atoms are C1, C2, C20, and C21 (the respective distances from Ag + are gradually 2.50, 2.48, 2.42, and 2.54 Å; see Fig.…”
Section: X-ray Crystallographysupporting
confidence: 64%
“…3. At this point it should be noted that the ''central'' cation Ag + is bound at the edges of the terminal [6]helicene aromatic rings, the corresponding hapticity of these bonds being g 2 , which follows from previous results by Lindeman et al [42]. The closest carbon atoms are C1, C2, C20, and C21 (the respective distances from Ag + are gradually 2.50, 2.48, 2.42, and 2.54 Å; see Fig.…”
Section: X-ray Crystallographysupporting
confidence: 64%
“…13 The R values observed for 1, i.e., 119.2°, 121.4°, and 119.5°, belong to none of these classifications and are rather similar to the angles (∼120°) observed in Ag-cyclic polyarene complexes, 14 in which the silver atom adopts a trigonal pyramidal geometry. It is not usual for Ag + to form a trigonal planar complex.…”
Section: Resultsmentioning
confidence: 60%
“…10 Theoretical calculations 17 indicated that the differences in binding energy between the η 1 -and η 2 -coordinations are quite small (<0.5 kcal mol -1 ) in silverbenzene complexes and that the silver ion can migrate on the entire π plane of benzene with virtually no activation barrier. Experimentally, η 1 -and η 2 -coordinations frequently coexist in the same crystal 13 and are sometimes observed even for the same silver atom. 10,18 In the present case, however, the silver atom is located above one of the carbon atoms of each benzene ring in a nearly η 1 -fashion, where the electron density is the highest.…”
Section: Resultsmentioning
confidence: 97%
“…Three modes of interaction can be envisaged: (i) the cation-p (arene) interaction via p-or s-binding modes (via employing a heteroatom) as described by Fukin et al for alkali metals, 38 (ii) the interaction of (poly)aromatic ligands via cation-p (arene) interactions with silver, 39 and (iii) the more classical complexation of silver by sulfur dithioethers. 40,41 The sulfur atom certainly plays a key role, as the Z moiety does not interact with silver cation, even though it is structurally similar to the S-benzyl thioether.…”
Section: Interaction Of Silver Ions With Peptidementioning
confidence: 99%